The Living Environmental Education Sound Science Toward a Cleaner, Safer, and Healthier Future - Fang, Wei-Ta.; Hassan, Arba'at.; LePage, Ben A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This open access book is designed and written to bridge the gap on the critical issues identified in environmental education programs in Asian countries. The world and its environments are changing rapidly, and the public may have difficulty keeping up and understanding how these changes will affect our way of life. The authors discuss various topics and case studies from an Asian perspective, but the content, messaging, and lessons learned need not be limited to Asian cultures. Each chapter provides a summary of the intensive research that has been performed on pro-environmental behaviors, the experience of people working in industry and at home, and their philosophies that guide them in their daily lives. We highlight humanity$1 (Bs potential to contribute to Sustainable Development Goals (SGDs) by understanding better the environmental psychology, social inclusion, and environmental sustainability and stewardship protection elements that contribute to responsible environmental citizenship. The content of the chapters in this book includes a discussion of the crucial issues, plans, and evaluations for sustainability theories, practices, and actions with a proposed management structure for maximizing the cultural, social, and ecological diversity of Asian experiences compared to other theories and cultures internationally. We intend that the data in this book will provide a comprehensive guide for students, professors, practitioners, and entrepreneurs of environmental education and its related disciplines using case studies that demonstrate the relationship between the social and behavioral sciences and environmental leadership and sustainability.s
Introduction to Environmental Education -- Environmental Education Research Method -- Environmental Literacy -- Environmental Psychology -- Environmental Paradigm -- Environmental Learning and Communication -- Outdoor Education -- Food Education -- Leisure Education -- Sustainable Development. .
Keywords: Environmental sciences -- Social aspects; Environmental education; Sustainability; Environmental Social Sciences; Environmental and Sustainability Education; Sustainability